2016
DOI: 10.1080/13603116.2016.1197326
|View full text |Cite
|
Sign up to set email alerts
|

The development and initial validation of a questionnaire of inclusive teachers’ competency for meeting special educational needs in regular classrooms in China

Abstract: The aim of this study was to develop and validate an instrument of inclusive teachers' competencies for teaching students with special educational needs in China. Data were obtained from a preliminary and large-scale investigation in Beijing. The primary analyses included exploratory factor analysis and confirmatory factor analysis. The findings indicated that Chinese inclusive teachers' competency is underpinned by four factors: teaching and instruction; communication and cooperation; attitudes and beliefs; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Or, it could be due to inefficient and ineffective prevention, provision, and treatment methods in the area of special education, resulting in high demand for special education provision. In this regard, prior research reported the need for further training for regular education teachers towards more inclusive education [18][19][20] (limitations of Learning in Regular Classrooms (LRC) [21][22][23][24]). Second, it is very interesting to see the number of total enrolment and graduates before and after the National Plan close to one another.…”
Section: Discussionmentioning
confidence: 99%
“…Or, it could be due to inefficient and ineffective prevention, provision, and treatment methods in the area of special education, resulting in high demand for special education provision. In this regard, prior research reported the need for further training for regular education teachers towards more inclusive education [18][19][20] (limitations of Learning in Regular Classrooms (LRC) [21][22][23][24]). Second, it is very interesting to see the number of total enrolment and graduates before and after the National Plan close to one another.…”
Section: Discussionmentioning
confidence: 99%
“…One may endlessly analyze experience of foreign countries (Deng, Wang, Guan, Wang, 2017;Altemueller, Lindquist, 2017;Rusznyak, Walton, 2017), debate on this issue, estimating these and those models of inclusive education (Scandinavian model, Swedish Model, American Model, Italian Approach) and the ways of their implementation. But one thing is beyond any doubts: the Russian Federation should follow its own way of inclusion development, taking into account its own peculiarities, opportunities, economic factor of each separate region, combining certain elements of already existing models and approaches, taking into account their pros and cons, advantages and disadvantages.…”
Section: Resultsmentioning
confidence: 99%
“…The data were analysed through exploratory factor analysis (EFA), using the Statistical Package for Social Sciences (SPSS) version 16.0, to determine groups of significant latent variables existing between items of the ICAQ. EFA allowed for the reduction of the size of a bank of items in order to identify the underlying dimensions of ICAQ [38].…”
Section: Analysis Of Datamentioning
confidence: 99%